Effect of Super Absorbent Polymer and Irrigation Deficit on Water Use Efficiency, Growth and Yield of Cotton - Hamid-Reza FALLAHI; Reza TAHERPOUR KALANTARI; Mahsa AGHHAVANI-SHAJARI; Mohammad-Ghasem SOLTANZADEH (Notulae Scientia Biologicae, 2015)
Sustainable use of water resources in agriculture is a necessity for many arid countries. In order to investigate the effect of water deficit, irrigation after 120 (control), 155 (moderate water stress) and 190 mm (sever water stress) pan evaporation and super absorbent polymer rates (SAP) (0, 30, 60 and 90 kg ha-1) on growth, yield and water use efficiency of cotton, an experiment was conducted as split plot based on a randomized complete block design with three replications. Moreover, the effect of water quality (distilled water and solutions of 0.25, 0.5, 0.75, 1 and 1.25% NaCl) was investigated on water holding capacity by SAP. Results revealed that moderate water stress (irrigation intervals of aprox. 15 days) along with 60 kg ha-1 SAP application was the best treatment in terms of growth and yield indices of cotton. The results for plant height, plant dry weight, boll number per plant and fiber yield in this treatment were 16, 28, 42 and 10% higher than control treatment, respectively. Water deficit and SAP application improved the water use efficiency (WUE) of cotton. The amount of WUE in moderate water stress treatment along with consumption of 60 or 90 kg ha-1 SAP was 26% higher than for control treatment. In addition, water holding capacity by SAP in distilled water treatment was 7 times higher than in the case of 1.25% NaCl solution. The overall results showed that irrigation deficit and SAP application are two appropriate strategies for crop production in areas affected by drought stress, especially if low saline water sources are used.